Theorising tourism in crisis: Writing and relating in place. (March 2021) - Gibson, Chris
Recent headline events – most notably the COVID-19 pandemic – have illustrated the fragility of tourism capitalism, prompting forward-looking analyses among critical scholars. While grappling with political and philosophical implications, commentaries have tended towards the prescriptive and general: contemplating the collapse of tourism as-we-know-it, and foregrounding opportunities to reconstitute more sustainable, resilient and inclusive forms of tourism. Heeding Haraway's call to 'stay with the trouble', I briefly outline three sympathetic critiques, integrating insights from more-than-human theory, disaster studies and climate change adaptation literatures. First, I unsettle temporalities of disruption and change that emphasise singular moments, such as lockdowns, rather than multiple temporalities of vulnerability and resilience. Second, a lurking species exceptionalism, which positions humans as the locus of agency, is contrasted with nonhuman capacities to shape unfurling events. Third, speculations on tourism's future that rest on normative categories, disembodied from lived experience, are contrasted with First Nations ontologies, and the messiness of tourism's relatings in place . Theorising tourism, within and beyond crisis, must evolve iteratively from the ethnographic. To illustrate, I 'write from' the east coast of Australia, where an otherwise steady-growth tourism economy has experienced profound disruption in 2020, not just from coronavirus-related travel restrictions, but from climate-change-amplified catastrophic bushfires. From this vantage point, multiple traumas refract tourism industry responses, while hope commingles with caution, tempering strident proclamations on the future. The nonhuman, political-economic, and emotional are inextricably entwined in the fabric of tourism. The fraught navigation of lived (more-than-human) experience must figure more prominently in our scholarly reckonings.